Lo público: experiencia urbana y metáfora ciudadana - Martín Barbero, Jesús (CIC. Cuadernos de Información y Comunicación, 2009)
The article treats the changes and adaptations that the concepts of Public Sphere and Public Space have suffered in Latin-American world, where the idealization of the State continues to make it more difficult to construct the public sphere. After the economical and socio-political crisis, we attend now to a new situation in which indigene communities reinvent the public space, either as by young urban groups. The author analyses different forms of action in the expression of public space in Bogotá, such as institutional programs or human movements, as well as the influence of new technologies to research which new forms of expression appear in the city.
Keywords: Latinoamérica; Identidad; Espacio urbano; Esfera pública; Crisis social; Cultura juvenil; Chat; Graffitis